THE RELATIONSHIP BETWEEN LOCUS OF EXTERNAL CONTROL AND CYBERLOAFING: THE ROLE OF ACADEMIC SELF-EFFICACY MEDIATION IN COLLEGE STUDENTS - Diah Charasati; Zakki Nurul Amin (LP2M IAI Al-Khairat Pamekasan, 2025)
The advancement of digital technology has increased the opportunities for university students to engage in cyberloafing, which refers to the use of the internet for non-academic activities during lectures. This study aims to analyze the relationship between external locus of control and cyberloafing behavior by examining the mediating role of academic self-efficacy. Using a correlational research design, data were collected from 345 students who completed scales measuring external locus of control, academic self-efficacy, and cyberloafing. Data were analyzed through bootstrapping techniques (N = 5000) using Hayes' PROCESS Model 4. The results indicate that external locus of control has a significant negative effect on cyberloafing (β = -0.36). However, academic self-efficacy partially mediates this relationship by exerting a positive indirect effect (β = 0.10). These findings suggest that although academic self-efficacy generally has beneficial effects, in certain contexts it may foster overconfidence that actually increases the tendency to engage in cyberloafing. This study highlights the importance of strengthening academic self-efficacy alongside self-control training to reduce deviant behaviors within digital learning environments.